The Mechanısm Of Elımınatıon Of Overbıte In Cases Treated By Begg Technıque - Hakan Gögen (Galenos Yayinevi, 1990)
In this study; interrelations between changes in dentofacial structure during overbite elimination in cases -who passed their active growth period- with excess overbite were tried to be evaluated. Measurements related with dental and skeletal structure were made on 30 pre and post treatment cephalometric films of research group consisted of 15 cases. Changes in measurements resulted from treatment were evaluated by correlation analysis.